A novel kernel functions algorithm for solving impulsive boundary value problems - Geng, F.Z.; Wu, X.Y. (Applied mathematics letters, 2022)
In this letter, to fit the character of solutions to impulsive boundary value problems (IBVPs), we firstly construct a piecewise continuous space using the reproducing kernel function (RKF) of smooth reproducing kernel Hilbert space (RKHS) W3. Then we present a fourth order convergent collocation approach for IBVPs by using the piecewise continuous basis functions yielded by RKFs in W3. Also, the convergence order of our approach is proved. The accuracy and convergence order are shown numerically.